Epidemiological Profile of the Victims of Sexual Violence Treated at a Referral Center in Southern Brazil - Santarem, Michelle Dornelles; Marmontel, Mariane; Pereira, Nathália Lima; Vieira, Letícia Becker; Savaris, Ricardo Francalacci (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective To characterize the sociodemographic profile of women victims of sexual violence treated at a university hospital in southern Brazil.Method The present cross-sectional study included all female victims of sexual violence who attended the sexual violence unit at the Hospital de Clínicas de Porto Alegre (HCPA, in the Portuguese acronym) from April 18, 2000 to December 31, 2017. Data were extracted from the electronic record of the patients and stored in a standardized questionnaire database with epidemiological aspects of the victim, the perpetrators and the type of aggression. Statistical analysis was performed using the chi-squared test for trend and descriptive statistics with 95% confidence interval (CI).Results During the length of the study, 711 women victims of sexual violence were treated. The mean age of the patients was 24.4 (±10) years old (range from 11 to 69 years old) and most of the victims were white (77.4%), single (75.9%) and sought care at the unit within 72 hours after the occurrence (80.7%). In most cases, violence was exerted by a single perpetrator (87.1%), who was unknown in 67.2% of cases. Victims < 19 years old showed a higher risk of not using contraception (relative risk [RR] = 2.7; 95% CI = 1.9–3.6).Conclusion Most victims of sexual violence were treated within 72 hours of the occurrence. The majority of these victims were white and young, and those < 19 years old had a higher risk of not using contraception and to know the sexual perpetrator.
Keywords: women's health service; violence against women; sexual violence; rape